2015
DOI: 10.1016/j.sleep.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin therapy for REM sleep behavior disorder: a critical review of evidence

Abstract: REM sleep behavior disorder (RBD) is a parasomnia associated with dream enactment often involving violent or potentially injurious behaviors during REM sleep that is strongly associated with synucleinopathy neurodegeneration. Clonazepam has long been suggested as the first-line treatment option for RBD. However, evidence supporting melatonin therapy is expanding. Melatonin appears to be beneficial for the management of RBD with reductions in clinical behavioral outcomes and decrease in muscle tonicity during R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(93 citation statements)
references
References 60 publications
1
82
2
8
Order By: Relevance
“…Melatonin appears to be beneficial for the management of RBD with reductions in clinical behavioural outcomes and a decrease in muscle tonicity during REM sleep. Melatonin also has a favourable safety and tolerability profile compared to clonazepam with limited potential for drug-drug interactions, which is an important consideration, especially in elderly individuals with RBD receiving polypharmacy, as adverse events were minimal [58].…”
Section: Effect Of Melatonin On Parasomniasmentioning
confidence: 99%
“…Melatonin appears to be beneficial for the management of RBD with reductions in clinical behavioural outcomes and a decrease in muscle tonicity during REM sleep. Melatonin also has a favourable safety and tolerability profile compared to clonazepam with limited potential for drug-drug interactions, which is an important consideration, especially in elderly individuals with RBD receiving polypharmacy, as adverse events were minimal [58].…”
Section: Effect Of Melatonin On Parasomniasmentioning
confidence: 99%
“…However, the mechanisms that underlie the beneficial effects of melatonin and ramelteon on RBD remain unclear. Some reports have suggested that melatonin might improve RBD due to direct inhibition of REM with atonia (RWA), inhibition of gamma-aminobutyric acid, stabilization of the circadian rhythm, improvement of sleep efficiency and/or modulation of skeletal muscles that have been inhibited by calmodulin (28). Moreover, it has been reported that melatonin protects exogenous L-dopa from autoxidation in the striatum of rats (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of action is unclear, melatonin may restore RBD-related desynchronization of circadian rhythms. In contrast to clonazepam, it is also shown to decrease the number of REM epochs without atonia and decrease both phasic and tonic motor activities [77,78]. Also, recent studies have shown favorability due to better side effect profile, with reduced falls and injuries when compared to clonazepam [74,79].…”
Section: Melatoninmentioning
confidence: 99%